Silicone-Organic Resin Hybrid Matrix Composites - Zhu, Bizhong; Wu, Yuhong; Reese, Herschel H.; Katsoulis, Dimitris E.; McGarry, Frederick J. (Macromolecular materials and engineering, 2006)
Glass fabric reinforced hybrid matrix composites of a toughened silicone resin and a vinyl ester resin were fabricated and their properties investigated. The hybrid composites consisted of multi‐layers of fiber reinforced silicone resins and vinyl ester resins. The toughened silicone resin, a crosslinkable phenylsilsesquioxane resin with high thermal and thermal oxidation resistance but relatively low Tg, was chosen to be the outer layers. The vinyl ester resin, with better strength, toughness and a much higher Tg than the toughened silicone resin, was used as the inner layers. A co‐cure process proved to establish a strong interface between the two in a hybrid composite. The hybrid composites had better flammability properties and much lower short term moisture absorption than the vinyl ester composites. The strength and modulus retention of the hybrid composites at elevated temperatures was higher than the composites using any single resin as the matrix. For example, when tested at 150 °C the flexural modulus and strength values of a twelve layer composite, with eight inner vinyl ester resin layers and four silicone outer layers, were almost an order of magnitude higher than the composite using the silicone resin alone, and were significantly higher than the one using vinyl ester resin alone. The room temperature short beam shear strength of the hybrid composites was also higher. DMA revealed that the inter‐diffusion of reactive components between the two resins was probably responsible for this synergistic effect, resulting in an α transition temperature of 182 °C for the hybrid composite, higher than that of either the silicone resin (85 °C) or the vinyl ester resin (162 °C).